Shock Analysis Method for Systematic Performance Evaluation of Component Embedded in Handheld Electronic Devices - C.S. Chin (Shock and Vibration)
It is important to identify the robustness of product (or embedded component inside the product) against shock due to free drop. With the increasing mobile and fast-paced lifestyle of the average consumer, much is required of the products; such as consumers expect mobile products to continue to operate after drop impact. Since free drop test is commonly used to evaluate the robustness of small component embedded in MP3 player, it is difficult to produce a repeatable shock reading due to highly uncontrolled orientation during the impact on ground. Hence attention has been focus on shock table testing, which produces a higher repeatable result. But it failed to demonstrate the actual shock with the presence of rotational movement due to free drop and also it suffers from a similar limitation of repeatability. From drop to drop, shock tables can vary about ± 5% in velocity change but suitable for making a consistent tracking the product improvement.